Penerapan Model Pembelajaran Kooperatif Scramble Terhadap Hasil Belajar Kognitif Siswa Kelas II SD pada Pembelajaran PPKn - Alyanti, Siti Elni; Ananthia, Winti; Furnamasari, Yayang Furi (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Problems in class II elementary school students show students' low knowledge of PPKn learning, symbol material and the practice of Pancasila as well as learning models that are not well developed by teachers in class II, which has an impact on students' cognitive learning outcomes. This research aims to measure the influence and differences in the application of the Scramble type cooperative learning model on the cognitive learning outcomes of class II elementary school students in PPKn learning. The research method used is a quasi-experimental design with a pre-test and post-test with non-equivalent control-group design involving experimental and control classes with a quantitative approach. Based on the research results, the scramble type cooperative learning model shows a significant influence on the cognitive learning outcomes of second grade elementary school students in PPKn learning with a significance value of <0.001 (smaller α= 0.05). The results of further research show that the difference in cognitive learning outcomes of students who use the scramble cooperative learning model is greater compared to students who use the conventional learning model, this can be seen from the results of the independent sample t-test with a significant value of 0.004 < 0.05.